The Dynamics of Social Change in Latin America - Veltmeyer, Henry. author. aut Link
XI, 210 p.
Keywords: This study examines fundamental theoretical and conceptual issues of social change in Latin America in the context of detailed empirical analysis. It challenges the major assumptions and propositions that underlie globalization theory, reworking and fine tuning the concepts of imperialism and social class as relevant to understanding the 'new world order'. The study centers on the structural features of Latin America and the state policies reconcentrating power in the capitalist class at the expense of labor. The study surveys the contradictory tendencies of concentrated wealth and power and the emergence of new socio-political movements and alternative development strategies to the dominant paradigm.